2021
DOI: 10.3390/nano11010090
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nanofluidic Cells Based on Nanowires and Nanotubes for Advanced Chemical and Bio-Sensing Applications

Abstract: Since the first introduction of one-dimensional nanochannels for single-molecule detection, there has been increasing interest in modern nanofluidic systems, such as chemical and biological sensing applications. Recently developed nanowires (NWs) and nanotubes (NTs) have received tremendous attention due to their unique geometrical, physical and chemical properties, which are very attractive in this field. Here, we review the recent research activities in the field of novel nanofluidic cells based on NWs and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 108 publications
2
14
0
Order By: Relevance
“…Nanochannels are ubiquitous structures that play key roles in both biological systems and artificial materials. The applications mainly include electrochemical sensing and biosensing ( Zhu et al, 2021 ), chip laboratory ( Pezzuoli et al, 2019 ), DNA sequencing ( Harrell et al, 2004 ; Fan et al, 2005 ), and other scientific frontiers. Nevertheless, the use of femtosecond laser technology to obtain structures with feature sizes fabrication less than 100 nm and aspect ratios higher than 20:1 on hard and brittle materials with high thermal and chemical stability, such as ceramics, sapphire, and glass, has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Nanochannels are ubiquitous structures that play key roles in both biological systems and artificial materials. The applications mainly include electrochemical sensing and biosensing ( Zhu et al, 2021 ), chip laboratory ( Pezzuoli et al, 2019 ), DNA sequencing ( Harrell et al, 2004 ; Fan et al, 2005 ), and other scientific frontiers. Nevertheless, the use of femtosecond laser technology to obtain structures with feature sizes fabrication less than 100 nm and aspect ratios higher than 20:1 on hard and brittle materials with high thermal and chemical stability, such as ceramics, sapphire, and glass, has rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced nanotechnologies and the trend of device miniaturization promote people to construct sophisticated nanostructures in different periodic arrangements and to explore their exciting physical and chemical phenomena. Highly ordered nanostructures will offer uniform size, morphology, and controllable particle distribution of nanomaterials. Therefore, light–matter interactions occurring on highly ordered arrays, for instance, surface lattice resonance (SLR), bring new properties and boost a wide range of applications in biochemical sensing, , plasmonics, , photoelectric conversion devices, , etc. Normally, ordered nanostructures can be classified by the lattice type, and square and honeycomb arrangements are two common lattice forms in two-dimensional nanoparticle arrays.…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue consists of twelve articles dedicated to nanofluid properties [ 1 ], the influence of nanoparticles on properties of other materials [ 2 , 3 , 4 ], as well as the possibility to enhance the heat transfer in different engineering devices using nanofluids, including the cooling of heat-generating elements in electronic devices [ 5 , 6 , 7 , 8 ], minichannel [ 9 ] and microchannel [ 10 ] optimization, and heat exchangers [ 11 , 12 ]. The objective of this Special Issue is to demonstrate the recent studies on nanoparticles and nanofluid applications in material treatment and engineering device optimization, which could be very useful for various specialists in mechanical and chemical engineering, physics, and mathematics.…”
mentioning
confidence: 99%
“…Thus, it has been revealed that the third-order nonlinear optical nature of metal/carbon nanosuspensions can be employed for developing dynamic nanoantennas. Zhu et al [ 4 ] have analyzed novel opportunities to employ nanowires and nanotubes in chemical and bio-sensing engineering devices. The authors have analyzed the synthesis techniques for nanowires and nanotubes, sensing mechanisms of nanofluidic devices based on nanowires and nanotubes, and some applications.…”
mentioning
confidence: 99%